DIFFERENT FORMS OF JOB SATISFACTION DOES JOB SATISFACTION MEAN SATISFIED EMPLOYEES? - Unterrainer, Christine; Jeppesen, Hans Jeppe; Jønsson, Thomas (Psyke & Logos, 2013)
This article introduces a qualitative model for different forms of job satisfaction that was originally proposed by Bruggemann, Grosskurth, and Ulich (1975), and further developed by Büssing (1992) and colleagues. This model is not new, but was probably buried in oblivion as a result of the longstanding and overwhelming dominance of the quantitative approach to job satisfaction in the English-speaking research community. We provide a brief historical overview on the quantitative research tradition of job satisfaction and basically discuss its methodological shortcomings. As an alternative, we describe different qualitative forms of job satisfaction according to Bruggemann et al. (1975) and Büssing (1992), and we additionally report some empirical results on the Bruggemann model. These findings suggest that the qualitative and quantitative approaches measure different aspects of job satisfaction, and that the integration of both approaches is a promising direction for future research. In the general discussion we propose some research perspectives and practical implications focusing on this integrative approach.